Coupled effect of B. Sphaericus bacteria and calcined clay mineral on OPC concrete. (2021) - Nagar, Prince Akash; Gupta, Nakul; Kishore, Kamal; Parashar, Arun Kumar
Abstract: The use of supplementary cementitious materials (SCMs) to partial replacement of Ordinary Portland Cement (OPC) is the most eminent strategy to reduce CO2 emissions in the global cement production industries. To achieve this, calcined clay can be considered as one of the efficient strategy to reduce CO2 emission. In this paper, calcined clay is used as SCMs in the partial replacement of cement in the proportion of 10%, 15%, and 20%. Moreover, for analyzing the self-healing characteristics of concrete, the provision of Bacillus Sphaericus bacteria with a bacterial count of 10 8 cells/ml is used along with calcined clay. Specimens were tested for water absorption and compressive strength at 7 days, 14 days, and 28 days respectively. The result reveals that bacteria embedded concrete used with partial replacement of calcined clay enhance the compressive strength by 21%, 24%, and 25% respectively at 28 days. Consequently, the bacteria embedded concrete with calcined clay grant less water absorption and enhance compressive strength of the concrete specimen; leads to the green and economic possibility for construction of concrete.